Water quality and pond soil analyses for aquaculture - Boyd, Claude E (Alabama Agricultural Experiment Station, Auburn University, 1992)
Water and soil analyses commonly needed in aquacultural research or in making decisions on water quality management in aquaculture ponds are described in this manual. Most procedures are useful in both freshwater and brackish water. In addition to providing a "step-by-step" account of each procedure, in most instances, some explanation of the basis of each is provided